Plasma microRNA-145-5p as a diagnostic biomarker for acute deep vein thrombosis - Christopher Antoun; Vårin Eiriksdatter Wikan; Øyvind Øverli; Thor Ueland; Gholamreza Jafari Yeganeh; Sigrid Kufaas Brækkan; Ellen Brodin; John-Bjarne Hansen (Research and Practice in Thrombosis and Haemostasis)
Background: Identification of new biomarkers for acute deep vein thrombosis (DVT) that could lower the need for diagnostic imaging to confirm or rule out the diagnosis would be advantageous. microRNA-145-5p (miR-145) has the potential to be a diagnostic marker for acute DVT, but its diagnostic performance has not been evaluated in consecutive patients referred to the hospital with suspected DVT. Objectives: The aim of this study was to assess the diagnostic performance of miR-145 for the diagnosis of acute lower extremity DVT. Methods: Patients consecutively referred to the emergency room at Akershus University Hospital (Norway) due to suspicion of acute DVT between June 2021 and July 2023 were included. Within 24 hours of admission, blood was collected for assessment of plasma miR-145 (index test), and whole-leg compression ultrasound (reference standard) was used to confirm or rule out DVT. Cohen’s d effect size and area under the receiver operating curve (AUC) were used to estimate the diagnostic performance of miR-145 and D-dimer. Results: Among 360 included patients, 101 (28%) were diagnosed with DVT. miR-145 showed poor diagnostic performance, as indicated by a Cohen’s d of −0.002 (95% CI, −0.241 to 0.216) and an AUC of 0.59 (95% CI, 0.51-0.67). For D-dimer, Cohen’s d was 1.66 (95% CI, 1.43-1.89), and the AUC was 0.92 (95% CI, 0.86-0.96). Conclusion: Plasma levels of miR-145 showed poor diagnostic performance for lower extremity acute DVT among persons referred to the emergency room with clinical signs and symptoms of DVT.